The THE RELATIONSHIP OF SOCIAL SUPPORT TO THE MENTAL HEALTH STATUS OF POST-CAESAREAN SECTION MOTHERS AT BHAYANGKARA HOSPITAL, JAMBI CITY - Simangunsong, Desi Ocianti; Mutmainnah, Muthia; Martawinarti, Rts Netisa; Yuliana, Yuliana; Meinarisa, Meinarisa (Program Studi Keperawatan Universitas Jambi, 2026)
Cesarean section is increasingly common worldwide and is associated not only with physical recovery challenges but also with psychological problems such as anxiety, stress, and depression in postpartum mothers. Social support is considered an important protective factor that may improve maternal mental health after childbirth. This study aimed to examine the relationship between social support and mental health status among post-cesarean mothers at Bhayangkara Hospital, Jambi City. This research employed a quantitative descriptive design with a cross-sectional approach involving 96 respondents selected using the Slovin formula. Data were collected through an online questionnaire using modified MSPSS and MHC-SF instruments. Validity and reliability tests confirmed that the instruments were appropriate for use. Data analysis included univariate and bivariate analysis using Kendall’s Tau-b test. The results showed that most respondents had high social support (61.5%) and high mental health status (60.4%). Statistical analysis revealed a positive and significant relationship between social support and mental health (τ = 0.384; p < 0.001). In conclusion, social support plays a significant role in improving mental health among post-cesarean mothers, although it is not the sole determinant. Strengthening support systems from family and healthcare providers is essential to enhance maternal psychological well-being.